2017
DOI: 10.1002/anie.201701358
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Siderophore–DOTAM Conjugates as Theranostics for Imaging and Treatment of Bacterial Infections

Abstract: There is a strong need to better diagnose infections at deep body sites through noninvasive molecular imaging methods. Herein, we describe the synthesis and characterization of probes based on siderophore conjugates with catechol moieties and a central DOTAM scaffold. The probes can accommodate a metal ion as well as an antibiotic moiety and are therefore suited for theranostic purposes. The translocation of the conjugates across the outer and inner cell membranes of E. coli was confirmed by growth recovery ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
150
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 36 publications
0
150
0
4
Order By: Relevance
“…This approach was further exploited by Brönstrup and co‐workers through the use of multivalent siderophore‐DOTA conjugates for targeting bacteria . The introduction of three O ‐acetyl‐2,3‐dihydroxybenzoic acid units on the DOTA scaffold via amide linkages made the resulting conjugate capable of capturing and firmly chelating iron (i.e., acting as a siderophore after hydrolysis of its acetate moieties by bacterial esterases and may be regarded as an enterobactin analog) .…”
Section: Non‐symmetrical Mpasmentioning
confidence: 99%
“…This approach was further exploited by Brönstrup and co‐workers through the use of multivalent siderophore‐DOTA conjugates for targeting bacteria . The introduction of three O ‐acetyl‐2,3‐dihydroxybenzoic acid units on the DOTA scaffold via amide linkages made the resulting conjugate capable of capturing and firmly chelating iron (i.e., acting as a siderophore after hydrolysis of its acetate moieties by bacterial esterases and may be regarded as an enterobactin analog) .…”
Section: Non‐symmetrical Mpasmentioning
confidence: 99%
“…[4,7] Die genauen Wechselwirkungen zwischen hydrolytischen und reduktiven Prozessen während der Eisenfreisetzung bleiben jedoch -s elbst in den besser charakterisierten bakteriellen Systemen -w eitestgehend unklar. [28] Danksagung Diese Arbeit wurde durch das D-A-CH-Programm (Deutsche Forschungsgemeinsschaft GR 1861/8-1 an M.G.u nd Wissenschaftsfonds FWF I1346-B21 an H.H.) [27] Aktuelle Studien beschäftigen sich bereits mit der Anwendung von Siderophor-Konjugaten bei der Bildgebung und Bekämpfung bakterieller Krankheiten, wovon eine die intrazelluläre Siderophor-Hydrolyse durch Esterasen als fürd ie zytotoxische Aktivitätz wingend notwendig beschreibt.…”
Section: Zuschriftenunclassified
“…[27] Aktuelle Studien beschäftigen sich bereits mit der Anwendung von Siderophor-Konjugaten bei der Bildgebung und Bekämpfung bakterieller Krankheiten, wovon eine die intrazelluläre Siderophor-Hydrolyse durch Esterasen als fürd ie zytotoxische Aktivitätz wingend notwendig beschreibt. [28] Stichwçrter: Eisenmetabolismus ·Hydrolyse ·P ilze · Siderophore ·T etraedrisches Intermediat…”
Section: Zuschriftenunclassified
“…[4,7] Thep recise interplay between hydrolytic and reductive processes during iron release however still remains uncertain, even in bettercharacterized bacterial systems. [28] Figure 5. [27] Regarding bacteria, recent studies have shown the use of diverse siderophore conjugates to image and combat infections,with one describing intracellular hydrolysis by esterases as being vital for the desired cytotoxic activity.…”
mentioning
confidence: 99%
“…[27] Regarding bacteria, recent studies have shown the use of diverse siderophore conjugates to image and combat infections,with one describing intracellular hydrolysis by esterases as being vital for the desired cytotoxic activity. [28] Figure 5. The architectureofthe active site differs significantly between the analyzed esterases.…”
mentioning
confidence: 99%